1985
DOI: 10.1093/sleep/8.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Heating During Sleep Interruption

Abstract: Summary: This study assessed the effects that elevating body temperature had on sleep structure in the third and fourth sleep cycles, cycles typically characterized by a high propensity for REM sleep and diminished levels of delta amplitude and incidence. The sleep of eight women and two men was interrupted for 30 min on each of 3 consecutive nights following an undisturbed adaptation night. The subjects were awakened each night following the end of the second REM sleep period. On 2 nights, subjects were immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…When individuals were passively warmed before nighttime sleep, SWS increased, either over the entire night or over its first part only. 8,9,23,29,30,32,47 The difference in SWS changes observed between daytime and nighttime sleep may be due to their circadian placements, which discourage its occurrence in the former condition. The propensity of REMS to occur is high at the end of the night and in the early hours of the day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When individuals were passively warmed before nighttime sleep, SWS increased, either over the entire night or over its first part only. 8,9,23,29,30,32,47 The difference in SWS changes observed between daytime and nighttime sleep may be due to their circadian placements, which discourage its occurrence in the former condition. The propensity of REMS to occur is high at the end of the night and in the early hours of the day.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of nocturnal sleep, it was reported that REMS proportions remained unaltered by a previous passive warming. 8,9,23,29,47,32 The invariance of REMS could be related to the fact that the short-term thermal loads used induced only transient hyperthermia whose effects never reached the end of the night (the time zone favorable for REMS occurrence). Hence, it could be interesting to see whether or not human nocturnal REMS could not be altered (nay enhanced) by a diurnal thermal stress prolonging its influence until the end of the night.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The after-effects of a passive thermal stress on nighttime sleep have been widely investigated, but exclusively under warm exposure. Passive warming occurring before bedtime provoked SWS increases over the entire night and/or over its first part (Bunnell and Horvath 1985;Bunnell et al 1988;Di Nisi et al 1989;Horne and Reid 1985;Jordan and Montgomery 1990;Shapiro et al 1989). The difference in SWS changes reported between daytime and nighttime sleep may be related to their circadian placements, which refrain SWS occurrence in the former condition.…”
Section: Sws Changesmentioning
confidence: 94%
“…Induced elevations of core body temperature by 2°C or more (Horne and Staff 1983;Horne and Reid 1985;Shapiro et al 1989) have been shown to increase SWS in the subsequent sleep episode, provided that this heat stress does not occur too close to sleep onset (Bunnell et al 1988). SWS can be induced to occur in the second half of a sleep episode by elevating core body temperature in the middle of the night (Bunnell and Horvath, 1985). Furthermore a positive correlation between core body temperature at the beginning of sleep and Correspondence: Dr D. G .…”
Section: Introductionmentioning
confidence: 99%